Acute fulminant necrotizing myopathy in a dog caused by co-infection with ultrastructural Sarcocystis caninum and Sarcocystis svanai-like apicomplexan protozoa - Hagner, Karolina; Jokinen, Tarja S.; Lavikainen, Antti; Sukura, Antti (Veterinary Parasitology, 2019)
Abstract Typically, carnivores are the definitive and herbivores the intermediate hosts for protozoan Sarcocystis spp. In the definitive host, the parasite has sexual multiplication in the intestine. Asexual phases occur in the musculature of different intermediate hosts. Although intestinal sarcocystosis is common in dogs, muscular symptomatic sarcocystosis is rarely reported. Here we report a fatal dual Sarcocystis spp. infection in a dog. The dog had acute onset of non-ambulatory tetraparesis. While neurological findings suggested a generalized neuromuscular disease with peripheral neuropathy concordant with the neurological deficits, the highly elevated muscle enzymes were more suggestive of a myopathy. Despite supportive therapy, the dog died three days after the onset of clinical signs. Necropsy revealed severe monophasic multifocal myodegeneration with severe pyogranulomatous inflammation. Histology revealed multiple sarcocysts in skeletal muscles and a smaller number in the heart. In light microscopy, both thin-walled and very thin-walled sarcocysts were found in skeletal muscles. Transmission electron microscopy confirmed the presence of two types of mature sarcocysts. Morphologically, cysts were indistinguishable from Sarcocystis caninum and Sarcocystis svanai, which were previously reported in a dog from USA. A region of the 18S rRNA gene sequence confirmed the presence of one species, S. arctica/caninum, without evidence for a dual infection. This is the first report of muscular sarcocystosis in a dog in Europe and, intriguingly, revealed morphologically similar species across the Atlantic. Peer reviewed